Comparative proteomic analysis of Ganoderma species during in vitro interaction with oil palm root - Said Hussin, Siti Nahdatul Isnaini (2017)
Basal Stem Rot (BSR) in oil palm caused by Ganoderma spp. is a deadly disease affecting oil palm plantation yield and global cooking oil supply. A pathogenic species, Ganoderma boninense is claimed as the main causal agent of BSR while Ganoderma tornatum is regarded as non-pathogenic and unable to infect living palms. Insufficient information on the infection mechanism and immature early detection strategy of the pathogen are among the disease control limitations. The existing molecular studies on the oil palm-Ganoderma interaction mainly focused on the response of the plant towards the fungus infection while the information on the pathogen responses is still a scarce. Therefore, in this study, response of the fungus at the infective stage during interaction with oil palm at the molecular level was investigated. An optimized protein extraction protocol for 2-Dimensional Electrophoresis (2-DE) gel analysis of Ganoderma spp. was developed and a comparative proteomic analysis were conducted to investigate the changes in the dikaryotic mycelial protein expression of the pathogenic G. boninense and non-pathogenic G. tornatum during in vitro interaction with oil palm root. The phenol/ammonium acetate in methanol was shown to be the most effective protein extraction method for 2-DE proteomic studies of Ganoderma spp. mycelia. Scanning Electron Microscope (SEM) images obtained confirmed the hyphae attachment and colonisation of both species on the oil palm root surface after 72 h of inoculation. Comparative proteomic analysis showed that the mycelial proteins from oil palm root exhibited different expression profiles when compared to the mycelia grown on Potato Dextrose Agar (PDA). Proteins differentially expressed in both species may have either direct or indirect link to virulence and pathogenicity, metabolism, growth and maintenance of both Ganoderma species. During the interaction, proteins with potential contribution to fungal pathogenicity such as enolase, alpha-aminoadipate reductase, carboxypeptidase, dienelactone hydrolase, glutamine synthetase (GS) and guanine nucleotide binding proteins (G proteins) were upregulated in G. boninense while bZIP protein, triose-phosphate-isomerase, redoxin and peroxiredoxin were mutually expressed in both species. Identification of these proteins during the interaction with oil palm roots may provide fundamental information for further investigation on specific roles of the identified proteins towards Ganoderma infection mechanism and facilitate selection of potential markers for early detection of BSR in the future.